indonesia Distribusi Kekayaan dalam Perspektif Ekonomi Makro Islam: Antara Keadilan dan Pertumbuhan: Distribusi Kekayaan dalam Perspektif Ekonomi Makro Islam: Antara Keadilan dan Pertumbuhan - elisa, ernina - (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze wealth distribution from the perspective of Islamic macroeconomics, focusing on the relationship between justice and economic growth. In Islamic economics, wealth is considered a trust that must be distributed fairly to achieve social welfare (falah). This paper employs a qualitative approach with a literature review focusing on Islamic macroeconomic theories and the principles of maqashid al-shariah. The findings show that fair wealth distribution forms the foundation of sustainable economic growth. Instruments such as zakat, infak, and waqf serve not only as redistribution mechanisms but also as drivers of economic productivity. Islamic economic policies based on distributive justice are shown to foster inclusive growth and reduce social inequality.